Weed survey in pivot irrigated soybean crop in Cachoeira do Sul - RS - Schmidt, Diogo André (2020)
The presence of weed species in soybean crops is a concern for farmers. Knowing these species is of great importance, as they cause serious damage to crops due to competition for nutrients, water, light and physical space with soy. This work aimed to survey weeds in pivot irrigated soybean crops in Cachoeira do Sul municipality, Capané district, in the experimental area of the Rio Grandense do Arroz Institute (IRGA). The evaluations were performed by applying the 0.25 m2 square method, launched at random sixty times. Weeds in the sampled areas were removed from the soil, species identified and quantified. Evaluations were performed after three applications of glyphosate herbicide. Even after glyphosate applications, seven species were identified, representing the families Asteraceae, Poaceae, Malvaceae, Euphorbiaceae and Rubiaceae. This survey enables the planning of preventive strategies for the sustainable control of weeds in the field, reducing production costs and the impact on the environment.